Flores de sombra - Apelfeld, Aharon (Serie Narrativa (Galaxia Gutenberg (Firm)) ;, 2012)
A haunting, heartbreaking story of love and loss. The ghetto in which the Jews have been confined is being liquidated by the Nazis, and Hugo is brought by his mother to the local brothel, where Mariana, one of the prostitutes, has agreed to hide him. As their lives spiral downward, Mariana reaches out for consolation to the boy who is on the cusp of manhood.